Analysis Of Potential Fraud Control At Metta Medika Hospital Sibolga - Erni Triyani Lubis; Juliandi Harahap; Nuraini Nuraini (Science Midwifery, 2021)
Health insurance is a guarantee in the form of health protection so that participants receive health care benefits and protection in meeting basic health needs that are given to everyone who has paid contributions or whose contributions are paid by the government. The problem that often occurs in health services is fraud. Fraud or in Indonesian better known as fraud, is something that is very likely to happen anywhere and in any form. The purpose of the study was to analyze the potential for fraud control at Metta Medika Hospital Sibolga. This study uses a descriptive qualitative method with a phenomenological approach to control potential fraud at Metta Medika Hospital Sibolga. This research was conducted at Metta Medika Hospital Sibolga. This research was conducted in November 2020–July 2021 starting with the submission of titles, preparation of proposals, proposal seminars, research, data processing, research results seminars, trial results and thesis revision. Research informants are 6 employees at Metta Medika Hospital Sibolga. Sources of data are carried out by means of in-depth interviews and field observations to formulate problems found by researchers at the research site. The results of the study show that the phenomenon that occurs is that fraud is a big challenge in companies including Metta Medika Hospital so that to prevent fraud, the anti-fraud section is involved to go directly to the field in terms of supervising, checking every document and evaluating every report given. If fraud is found, it will be resolved immediately by involving the management and director of the Hospital to impose sanctions on the perpetrators of fraud in terms of the size of the fraudulent act committed and immediately evaluate all related parties to complete it. Suggestions for hospitals to be more aware of the potential for fraud that can be carried out by everyone so it is necessary to develop a system to prevent fraud at Metta Medika Sibolga Hospital. The next researcher becomes a reference for further qualitative research regarding the incidence of fraud in companies and hospitals with a larger number of participants and more in-depth interviews.